Analisis dan Perancangan Sistem Informasi Jasa Titip Berbasis Web: TitipGo - Dwi Resty Kartika; Sinta Febriyanti; Siti Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2025)
The design of a web-based information system addresses issues in proxy shopping services (jastip), which are often conducted manually via social media and prone to fraud. This study introduces Titipgo, a platform enabling secure, efficient, and structured transactions. The methodology includes PIECES analysis to identify system weaknesses and UML modeling (use case and activity diagrams) for design. The system supports four roles: admin, proxy shopper (jastiper), buyer, and owner, with core features like account management, product catalog, order tracking, payment processing, and reviews. A responsive UI was prototyped in Figma, tailored for each user role. Results confirm Titipgo enhances professionalism and trust in proxy shopping operations. This system sets a foundation for improving security and efficiency in collaborative e-business.